Inovasi Media Permainan Edukatif dari Limbah untuk Ikatan Guru Aisyiyah Bustanul Athfal - Diana Diana; Sudarti; Nabila; Hanum Mukti Rahayu (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
This community service activity aims to enhance the competency of teachers in creating Educational Play Tools (APE) from waste materials at TK Aisyiyah Bustanul Athfal Kubu Raya. Early childhood education involves learning through play, making APE an essential component in the learning process. This activity was conducted on September 20, 2023, at the Auditorium of Muhammadiyah University Pontianak, involving 15 teachers from 8 institutions affiliated with the Aisyiyah Bustanul Athfal Teachers' Association (IGABA) Kubu Raya. The methods used included lectures, demonstrations, and Q&A sessions. The training consisted of three stages: providing material on APE, practical APE creation, and mentoring and monitoring. Evaluation was conducted using participant response questionnaires, covering four indicators: previous training experience, increased environmental awareness, new knowledge gained, and the ability to create APE after the training. The results showed that 100% of the participants could create and use APE in their teaching. Additionally, the training provided a new experience for 66.7% of the participants who had never attended similar training before. APEs were made from recycled materials such as cardboard, plastic bottles, and fabric, also raising participants' environmental awareness. In conclusion, this training effectively improved teachers' competency in creating APE, which is expected to enhance the quality of early childhood education at TK Aisyiyah Bustanul Athfal Kubu Raya. Documentation of APE usage in schools demonstrated successful implementation, with various types of APE designed to activate different aspects of child development.